Small-molecule Modulation of HDAC6 Activity: The Propitious Therapeutic Strategy to Vanquish Neurodegenerative Disorders - A. Ganai, Shabir (Current Medicinal Chemistry, 2017)
Histone deacetylases (HDACs) are epigenetic enzymes creating the transcriptionally inactive state of chromatin by erasing acetyl moiety from histone and non-histone substrates. HDAC6 modulates several biological pathways in dividing cells as well as in post-mitotic neurons, and has been implicated in the pathophysiology of neurodegeneration. The distinct cellular functions and survival in these cells are reliant on HDAC6-mediated processes including intracellular trafficking, chaperone-mediated stress responses, anti-oxidation and protein degradation. Consequently, the interest in HDAC6 as a promising therapeutic target to tackle neurodegenerative disorders has escalated markedly over the last decade. Taking these grim facts into consideration, the current article focuses on structural organization of HDAC6. Importantly, we discuss the general role of HDACs in cognition and neuronal death. Further, we describe the unique involvement of HDAC6 in eliminating protein aggregates, oxidative stress and mitochondrial transport. Moreover, the article rigorously details how the impaired activity of HDAC6 culminates in neurodegenerative complications like Alzheimer disease (AD), Parkinson's disease (PD), Huntington's disease (HD), amyotrophic lateral sclerosis (ALS) and spinal muscular atrophy (SMA). Lastly, we provide crystal clear view regarding the fascinating research areas which may lead to the development of novel small-molecules for enhanced therapeutic benefit against these therapeutically arduous neurodegenerative maladies.
Keywords: PD